Double-balloon tamponade in the management of postpartum hemorrhage: a case series - Kavak, Salih Burin; Kavak, Ebru Celik; Demirel, Ismail; Ilhan, Rasit (Dove Medical Press Ltd, 2014)
To show the efficacy of double-balloon cervical ripening catheter in the management of postpartum hemorrhage originating from the lower segment of the uterus or the upper parts of the vagina. Methods: Patients with intractable bleeding from the lower segment of the uterus and the upper parts of the vagina after Cesarean or vaginal deliveries were treated by double-balloon cervical ripening catheter. Results: Double-balloon catheter was used in seven patients, and it was properly placed in all of them. No other intervention was needed to control bleeding. Two patients were delivered vaginally, and five patients were delivered by Cesarean section. Length of hospitalization was longer in the vaginal delivery patients (average hospitalization was 12 days in the vaginal delivery patients and 5 days in the Cesarean section patients). The need for blood and blood products transfusion (average of blood and blood products transfusion was 30 U in the vaginal delivery patients and 6 U in the Cesarean patients) was also higher in the vaginal delivery patients. Conclusion: Although double-balloon cervical ripening catheter is designed for the induction of labor, it can successfully control intractable bleedings from the lower segment of the uterus and the upper parts of the vagina. This procedure can save patients from undergoing more morbid procedures.
Keywords: cesarean section; double-balloon catheter; postpartum hemorrhage; vaginal delivery